EFFECT OF P-COUMARIC ACID AGAINST OXIDATIVE STRESS INDUCED BY CISPLATIN IN BRAIN TISSUE OF RATS - F. N. Ekinci-Akdemir; İ. Gülçin; C. Gürsul; S. H. Alwasel; Y. Bayir (Journal of Animal and Plant Sciences, 2017)
The antioxidant effect of p-Coumaric acid was evaluated against brain damage induced by cisplatin in rats. In this experimental study, twenty-four Sprague-Dawley rats were divided into four groups; control, p-Coumaric acid, cisplatin, and p-coumaric acid+cisplatin. Cisplatin was administered intraperitoneally (i.p) in a single dose of 10 mg kg-1. p-Coumaric acid was given in a doses of 100 mg kg−1i.p. for three days. In the cisplatin group, rats were sacrificed under anesthesia after 72 hours administration of cisplatin and brain tissues were removed. To assess the changes in biochemical aspects, activities of superoxide dismutase and level of malondialdehyde, glutathione were measured. An increase on activities of superoxide dismutase and level of glutathione has been observed in the group applied p-coumaric acid+cisplatin when compared with the cisplatin group. Moreover, the p-coumaric acid+cisplatin group had lower level of malondialdehyde compared to that of the cisplatin group. In conclusion, our results indicated that p-coumaric acid can mitigate cisplatin-induced oxidative damage in brain tissue.
Keywords: p-Coumaric acid; Cisplatin; Oxidative Stress; Brain; Rats